GAMBARAN KUALITAS TIDUR DAN FUNGSI KOGNITIF PADA PASIEN PPOK DI BBKPM MAKASSAR - Budiman, Arif; Majid, Abdul; Syam, Ilham; Efendi, Suradi (Jurnal Kesehatan, 2021)
Poor sleep quality in patients with Chronic Obstructive Pulmonary Disease is caused by shortness of breath, coughing and excessive secretion production. Someone who has good sleep quality will affect his cognitive function, where sleep stage is associated with cerebral blood flow. Increased oxygen consumption can help store memory and learning related to cognitive function. Disorders of cognitive function will affect someone’s productivity and even loss of independence. The incidence of COPD increases every year. By BBKPM 2015 that there were 130 patients, 142 in 2016 and 182 in 2017. This study aimed to describe the quality of sleep and cognitive function in COPD patients.This was descriptive study in that number of sample was 52 from 182 populations diagnosed with COPD at BBKPM Makassar. Data collection applied PSQI questionnaires to measure sleep quality and MMSE questionnaire to measure cognitive function.The results revealed that from 52 respondents, 35 (67.3%) performed poor sleep quality while 17 (32.7%) had good sleep quality with average score on PSQI 6.92. In addition, from 52 respondents, 29 (55.8%) had impaired cognitive function while 23 (44.2%) had normal cognitive function with average score on MMSE 22.77.It concluded that patients with COPD experienced poor sleep quality and cognitive impairment. It is encouraged to COPD patients to reduce strenuous activities in order to avoid shortness of breath.